Development of Jawi Arabic Chemistry Module on Atomic Structure Material at Al-Muslimun Integrated Dayah Lhoksukon - Zakiyah, Hayatuz; Emda, Amnda; Thahira, Haniyya (Indonesian Journal of Education and Social Humanities, 2024)
The development of the Jawi Arabic chemistry module on atomic structure material which was carried out at Dayah Terpadu Al-Muslimun Lhoksukon was motivated by the absence of a chemistry module that uses Indonesian or Jawi Arabic, therefore researchers are interested in developing the Jawi Arabic chemistry module as one of the latest innovations that can increase students' interest in learning. The aim of this research is to determine the feasibility of the product and students' responses to the Arabic Jawi chemistry module being developed. The subjects used were class X science students, the sample was 20 Islamic boarding school students and female students. The research method used is Research and Development (R&D) and uses the Borg and Gall model. Data collection techniques were carried out using interview questionnaires as initial needs analysis, product validation questionnaires, and student response questionnaires. Data analysis of validation results and response questionnaires uses a percentage formula. The results of the validation of the Jawi Arabic Chemistry module reached an average percentage of 87.6% in the "very feasible" category and the student response results reached a percentage of 91.92% in the "very good" category. Based on the research results, it can be concluded that the development of the Jawi Arabic chemistry module on atomic structure material is suitable for use as an additional reading reference in Dayah Terpadu Al-Muslimun Lhoksukon.